EPOCK study protocol: a mixed-methods research program evaluating cancer care coordination nursing occupations in France as a complex intervention - F. Colombani; M. Sibé; M. Kret; B. Quintard; A. Ravaud; F. Saillour-Glénisson (BMC, 2019)
Abstract Background Facing the increasing cancer incidence and cancer survivorship, many national strategic cancer plans have identified cancer care coordination as a priority for health service improvement. However, the high variability of practices, the diversity of definitions and underlying concepts increases the existing difficulty to standardise, replicate, transpose and assess care coordination within the French health system context. The EPOCK national study aims at evaluating practices and the working context of hospital-based cancer care coordination nurses, based on a previously designed reference framework for care coordination within the French health system context. Methods EPOCK is based on a comprehensive evaluation of nursing professions in cancer care coordination, considered as a complex intervention. Phase 1 (theoretical phase) will define and design a theoretical reference framework for care coordination in France through an international literature review, aiming to identify relevant models and all components of the expected framework and a structured consensus method, the Nominal group technique, aiming to select and prioritise the most relevant components already found in the literature review with regard to the French healthcare system; phase 2 (Operational phase) will consist in an in-depth analysis of practices, contexts, perceptions and attitudes related to care coordination occupations by nurses in oncology and all stakeholders (related professionals, patients and their caregivers) through a multicentric cross-sectional mixed-method evaluative study. The observed practices and contexts will be finally compared with the theoretical reference framework using both inductive and deductive approaches. Discussion This study will result in an evaluation framework identifying key models and key elements relative to cancer care coordination interventions that can be used to guide management of cancer care coordination nursing occupations within the French healthcare system. EPOCK would also assist in public decision-making to identify optimal targets, skills profiles and scope of actions for cancer coordination professions. Finally, EPOCK will describe typology of nurse practices in cancer care coordination and thus obtain precise preliminary information essential for drafting a medico-economic evaluation study of these new nursing professions' impact. Trial registration Clinicaltrial.gov registration: NCT03350776, 11/22/2017.